1998
DOI: 10.1523/jneurosci.18-15-05594.1998
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for a Small Synaptic Vesicle-Associated Phosphatidylinositol 4-Kinase in Neurotransmitter Release

Abstract: Glutamate release from nerve terminals is the consequence of Ca2+-triggered fusion of small synaptic vesicles with the presynaptic plasma membrane. ATP dependence of neurotransmitter release has been suggested to be founded, in part, on phosphorylation steps preceding membrane fusion. Here we present evidence for an essential role of phosphatidylinositol phosphorylation in stimulated release of neurotransmitter glutamate from isolated nerve terminals (synaptosomes). Specifically, we show that a phosphatidylino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
4

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 58 publications
6
72
0
4
Order By: Relevance
“…Our results confirm the existence of a PI 4-kinase activity on synaptic vesicles (19) and identify the enzyme responsible for this activity as PI4KII␣. We further show that this enzyme accounts for the bulk of the PI 4-kinase activity in a brain extract and is present at high concentration at synapses.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results confirm the existence of a PI 4-kinase activity on synaptic vesicles (19) and identify the enzyme responsible for this activity as PI4KII␣. We further show that this enzyme accounts for the bulk of the PI 4-kinase activity in a brain extract and is present at high concentration at synapses.…”
Section: Discussionsupporting
confidence: 83%
“…In vitro lipid phosphorylation assays on cytosol, immunoprecipitated kinases, or recombinant purified kinases were performed as described with minor modifications (18). In a typical assay, the reaction mixture (50 l) contained 30 mM Hepes (pH 7.4), 100 mM KCl, 2 mM MgCl 2 , 1 mM EDTA, [10][11][12][13][14][15][16][17][18][19][20] g of substrate lipid [synthetic short chain phosphoinositides (Echelon, Salt Lake City) or a brain-derived phosphoinositide mixture (Sigma P-6023)], and 0.2% Triton X-100. The reaction was initiated by addition of 40 M ATP (10 Ci of [␥-32 P]ATP per assay; 1 Ci ϭ 37 kBq) and performed for 10 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…To rule out any long-term effect of PI3K activity on this process, chromaffin cells were treated for 24 h in culture medium with LY294002 (1 M) without significant consequence on evoked catecholamine release (see supplementary material S1). Together, these experiments seem to exclude any direct involvement of most subtypes of PI3K in neuroexocytosis, as previously established in neurosecretory cells and synaptosomes (Wiedemann et al, 1996;Martin et al, 1997;Wiedemann et al, 1998). However, one PI3K isoform, type II PI3K-C2␣, is much less sensitive to these EE-tagged PI3K-C2␣ was transiently expressed in COS cells and immunoprecipitated with anti-EE monoclonal antibodies followed by protein A-Sepharose.…”
Section: Resultssupporting
confidence: 69%
“…However, a direct involvement of this class of enzymes and their lipid products in neuroexocytosis has been questioned Milosevic et al, 2005), based on little or no observed inhibition of synaptosomal or neurosecretory cell exocytosis by the PI3K inhibitors wortmannin and LY294002 (Wiedemann et al, 1996;Martin et al, 1997;Wiedemann et al, 1998). However, at the neuromuscular junction, wortmannin was shown to inhibit both spontaneous and evoked quantal neurotransmitter release (Hong and Chang, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…PtdIns4K activity is found on chromaffin granules and on small synaptic vesicles and is required for vesicle fusion (386,387). PtdIns4K activity is also found on vesicles containing the Glut4 glucose transporter isolated from muscle (190).…”
Section: Ptdins4kiii␤/pik1mentioning
confidence: 99%